2020
DOI: 10.7554/elife.51972
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal patterns of neocortical activity around hippocampal sharp-wave ripples

Abstract: A prevalent model is that sharp-wave ripples (SWR) arise ‘spontaneously’ in CA3 and propagate recent memory traces outward to the neocortex to facilitate memory consolidation there. Using voltage and extracellular glutamate transient recording over widespread regions of mice dorsal neocortex in relation to CA1 multiunit activity (MUA) and SWR, we find that the largest SWR-related modulation occurs in retrosplenial cortex; however, contrary to the unidirectional hypothesis, neocortical activation exhibited a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 86 publications
12
110
1
Order By: Relevance
“…In this view, the higher accumulation of angles at 0 degrees observed when comparing force vs non force events could represent the hallmark of such network switch. Interestingly, a similar propagation pattern has been observed applying optical flow analysis to calcium imaging over the same cortical areas when windowing cortical activity around hippocampal sharp wave ripples during sleep (Karimi Abadchi et al, 2020) and corresponds to one of the two major propagation patterns observed during slow wave sleep (Greenberg et al, 2018). Our findings extend these results to the awake condition during motor execution.…”
Section: Cortical Propagation Features In Healthy Micesupporting
confidence: 82%
“…In this view, the higher accumulation of angles at 0 degrees observed when comparing force vs non force events could represent the hallmark of such network switch. Interestingly, a similar propagation pattern has been observed applying optical flow analysis to calcium imaging over the same cortical areas when windowing cortical activity around hippocampal sharp wave ripples during sleep (Karimi Abadchi et al, 2020) and corresponds to one of the two major propagation patterns observed during slow wave sleep (Greenberg et al, 2018). Our findings extend these results to the awake condition during motor execution.…”
Section: Cortical Propagation Features In Healthy Micesupporting
confidence: 82%
“…Glutamate is an important neurotransmitter that regulates neural activity and cerebral metabolism during wakefulness and sleep. However, much of the previous work studying extracellular release has been done using fixed-potential amperometry 43 , or optical imaging in head-fixed mice 44 . Inducing sleep in head-fixed mice is challenging and typically requires sleep deprivation which can alter the overall sleep structure and patterns of rapid eye-movement (REM) and non-REM (NREM) sleep 45,46 .…”
Section: Imaging Glutamate Release Dynamics During Wakefulness and Namentioning
confidence: 99%
“…Inducing sleep in head-fixed mice is challenging and typically requires sleep deprivation which can alter the overall sleep structure and patterns of rapid eye-movement (REM) and non-REM (NREM) sleep 45,46 . The design flexibility of the See-Shells allowed us to incorporate local field potential (LFP) recording electrodes in the dorsal hippocampus in Emx-CaMKII-Ai85 mice, expressing iGluSnFR in glutamatergic neocortical neurons 33,44,47 . Mice were allowed to naturally transition to sleep in their home cage.…”
Section: Imaging Glutamate Release Dynamics During Wakefulness and Namentioning
confidence: 99%
“…Therefore, SWR interval is not likely the cause of the differential post-SWR cortical activity pattern in ENR. Of note, we also analyzed urethane anesthetized mice (Karimi Abadchi et al, 2020) and found that results were distinct to natural sleeping mice regardless of rearing conditions (ISO, normal caged mice (NOR), and ENR; Figure 4). The results suggest that the distinct activity patterns between awake and sleep state are likely to be caused by natural awake/sleep cycles.…”
Section: Resultsmentioning
confidence: 99%